2019
DOI: 10.1021/acs.jafc.9b01001
|View full text |Cite
|
Sign up to set email alerts
|

Non-targeted Metabolomic Analysis Based on Ultra-High-Performance Liquid Chromatography Quadrupole Time-of-Flight Tandem Mass Spectrometry Reveals the Effects of Grafting on Non-volatile Metabolites in Fresh Tea Leaves (Camellia sinensis L.)

Abstract: To investigate the effects of grafting on non-volatile metabolites in tea, non-targeted metabolomic analyses of fresh leaves were performed on the basis of ultra-high-performance liquid chromatography quadrupole time-of-flight tandem mass spectrometry (UHPLC−QTOF/MS). One non-grafted YingHong No. 9 and four grafted tea [grafting scion YingHong No. 9 on four different rootstocks, BaiMao No. 2 (BM2), BaiYeDanCong (BY), HeiYeShuiXian (HY), and WuLingHong (WLH)] were chosen as materials. In total, 32 differential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…In this way, tea samples were all made using fresh tea leaves from grafted tea trees, and they still showed consistency with YJ on aroma quality, with HZX as an exception. Under this condition, it could be concluded that tea aroma quality was mainly influenced by rootstocks, which meant that grafting on different rootstocks might change the components of scions differently (Qi et al., 2019) and thus changed the aroma quality of made tea differently. In other words, grafting could change aroma quality with marked/slight difference of the made tea and the variations were decided by different rootstocks.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In this way, tea samples were all made using fresh tea leaves from grafted tea trees, and they still showed consistency with YJ on aroma quality, with HZX as an exception. Under this condition, it could be concluded that tea aroma quality was mainly influenced by rootstocks, which meant that grafting on different rootstocks might change the components of scions differently (Qi et al., 2019) and thus changed the aroma quality of made tea differently. In other words, grafting could change aroma quality with marked/slight difference of the made tea and the variations were decided by different rootstocks.…”
Section: Resultsmentioning
confidence: 98%
“…Tea is a kind of product produced from fresh leaves, the compound in which is the foundation of sensory quality of tea. Previous study suggested that grafting did influence metabolites in fresh tea leaves (Qi et al., 2019); however, our main focus now was to investigate whether grafting could have an impact on the quality of made tea. As a result, we decided to investigate whether grafting could influence the aroma quality of the made tea produced under the same parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Two isomeric compounds at rt 2.90 and 3.75 min (entries 2 and 5) showed the precursor ion at m / z 289.0705 [M – H] − in the negative ionization mode and 291.0871 [M + H] + in the positive ionization mode, resulting in a chemical formula of C 15 H 14 O 6 . The fragment ions were observed at m / z 245, 203, 151, 137, and 125. , Based on the parent and fragment ions observed, the compounds were tentatively identified as catechin and epicatechin. , The compounds eluting at rt 2.59, 3.02, and 3.36 min (entries 1, 3 and 4) were identified as possible isomers of B-type procyanidin. They showed a precursor ion at m / z 577.1347 [M – H] − in the negative ionization mode and 579.1520 [M + H] + in the positive ionization mode, giving a chemical formula of C 30 H 26 O 12 for the compounds.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The fragment ions were observed at m / z 245, 203, 151, 137, and 125. 17 , 18 Based on the parent and fragment ions observed, the compounds were tentatively identified as catechin and epicatechin. 17 , 18 The compounds eluting at rt 2.59, 3.02, and 3.36 min (entries 1, 3 and 4) were identified as possible isomers of B-type procyanidin.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation